SALIVARY ANTIMICROBIAL PROTEIN RESPONSE TO PROLONGED RUNNING - Suzanne Schneider; Karol Dokladny; Cheryl Gourley; Matthew Kuennen; Trevor L Gillum (Termedia Publishing House, 2013)
Prolonged exercise may compromise immunity through a reduction of salivary antimicrobial proteins (AMPs). Salivary IgA (IgA) has been extensively studied, but little is known about the effect of acute, prolonged exercise on AMPs including lysozyme (Lys) and lactoferrin (Lac). Objective: To determine the effect of a 50-km trail race on salivary cortisol (Cort), IgA, Lys, and Lac. Methods: 14 subjects: (6 females, 8 males) completed a 50km ultramarathon. Saliva was collected pre, immediately after (post) and 1.5 hrs post race ( 1.5). Results: Lac concentration was higher at 1.5 hrs post race compared to post exercise (p<0.05). Lys was unaffected by the race (p>0.05). IgA concentration, secretion rate, and IgA/Osm were lower 1.5 hrs post compared to pre race (p<0.05). Cort concentration was higher at post compared to 1.5 (p<0.05), but was unaltered from pre race levels. Subjects finished in 7.81 ± 1.2 hrs. Saliva flow rate did not differ between time points. Saliva Osm increased at post (p<0.05) compared to pre race. Conclusions: The intensity could have been too low to alter Lys and Lac secretion rates and thus, may not be as sensitive as IgA to changes in response to prolonged running. Results expand our understanding of the mucosal immune system and may have implications for predicting illness after prolonged running.